Service Quality Evaluation in the Internal Supervision Department and the Level of Customer Satisfaction "Applied Study on Baron Hotel" - Talib Mahdi AL. Agele, Ahmed; Kadhim Shamram, Muntadher; Ubed Faraj, Dhafir (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the service quality evaluation provided in the hotel supervision department and its relation to customer satisfaction through the Baron Hotel as a case study. The researchers followed the analytical descriptive method to suit to the nature of the study. The questionnaire was implemented and designed as a tool for collecting data and distributing it to the sample of the study, represented by 86 guests of the Baron Hotel, where the questionnaires were sorted and collected, the questionnaires were valid are (72). The researcher used the statistical methods through (20 SPSS) program. The study come up of several results, including that the sample of the study evaluated , the service provided by the internal supervision department in this hotel in the light of the quality standards of hotel services positively. There were no differences in costumer indication according to income, educational level, age, and marital status. The Baron's internal supervision service leads to customer satisfaction. The study recommended a set of recommendations aimed at developing the service in the hotel supervision department, the most important of which is: The management of the Baron Hotel should work on training the hotel staff in the latest scientific and practical methods and taking into account the possible problems in the hotel supervision department.